Association between sarcopenic obesity and mortality in patients on peritoneal dialysis: a prospective cohort study - Shen, Yiwei; Su, Xinyu; Yu, Zanzhe; Yan, Hao; Ma, Dahua; Xu, Yimei; Yuan, Jiangzi; Ni, Zhaohui; Gu, Leyi; Fang, Wei (Frontiers in Medicine, 2024)
Background Whether sarcopenic obesity had unfavorable effect on survival of peritoneal dialysis (PD) patients is unknown. We aimed to investigate the association between sarcopenic obesity and survival in PD patients. Methods This was a prospective observational study. Eligible PD patients from November 2016 to December 2017 were enrolled and followed until August 31, 2023. Sarcopenia was defined following the recommendations of the Asian Working Group for Sarcopenia (AWGS) as low appendicular skeletal muscle mass index (ASMI) and handgrip strength (HGS). Obesity was defined using the percentage of body fat (PBF). Survival analysis was conducted using the Kaplan–Meier and log-rank test. The Cox regression and the cumulative incidence competing risk (CICR) analyzes were used to investigate the association between sarcopenic obesity and all-cause mortality. Results A total of 223 patients were enrolled with 133 (59.6%) males, a median age of 57.5 (44.6, 65.7) years, a median dialysis vintage of 20.3 (6.4, 57.7) months and 48 (21.5%) who had comorbid diabetes mellitus. Among them, 46 (20.6%) patients were sarcopenic, and 25 (11.2%) patients were diagnosed with sarcopenic obesity. After followed up for 51.6 (25.6, 73.9) months, the Kaplan–Meier curve showed the sarcopenic obesity (log-rank = 13.527, p < 0.001) group had significant lower survival rate compared to the nonsarcopenic non-obesity group. For multivariate analysis, the CICR method showed patients with sarcopenic obesity had significantly higher mortality rate (HR: 2.190, 95% CI: 1.011–4.743, p = 0.047) compared to those with nonsarcopenic non-obesity. Conclusion Sarcopenia is not uncommon in PD patients, with a considerable proportion having sarcopenic obesity. There is a significant association between sarcopenic obesity and an increased risk of mortality in PD patients.